Gestational obesity and subclinical inflammation: The pathway from simple assessment to complex outcome (STROBE-compliant article). Issue 20 (21st May 2021) - Rugină, Cosmin; Mărginean, Cristina Oana; Meliţ, Lorena Elena; Huţanu, Adina; Ghiga, Dana Valentina; Modi, Viviana; Mărginean, Claudiu
Abstract : Abstract: Maternal obesity and excessive gestational weight gain (GWG) are associated with pregnancy-related complications, poor birth outcomes, and increased birth weight (BW). The aims of this study were to assess the relationship between excessive GWG and gestational inflammatory status in terms of blood parameters, as well as its influence on newborn's outcomes. We performed a prospective study on 176 pregnant women divided into 2 groups depending on the GWG: group 1—normal GWG, 80 cases; and group 2—high GWG, 96 cases. The statistical analysis was performed using the GraphPad Prism program, trial variant. We performed a thorough anamnesis and clinical examination in all mothers and their newborns, as well as an assessment of multiple laboratory parameters. The levels of both platelets and triglycerides were significantly higher in pregnant women from high GWG group ( P  = .0165/ P  = .0247). The newborns whose mothers presented an excessive GWG were found with a significantly higher BW as compared to those with normal GWG mothers ( P  = .0023). We obtained a positive correlation between the mothers' and newborns' values for hemoglobin, high-density lipoprotein, leucocytes, and platelets/lymphocytes ratio ( P  = .0002/ P  = .0313/ P  = .0137). Moreover, a significant positive correlation was found between GWG and BW ( r  = 0.2049, 95% CI: 0.0588–0.3425, P  = .0064). Our findings sustain the hypothesis that maternal obesity is a risk factor for macrosomia and childhood obesity since we found a positive correlation between GWG and BW. Women with high GWG expressed significantly higher levels of platelets and triglycerides suggesting a subclinical inflammation associated to excessive fat accumulation. The inflammation transfer from mother to fetus in our study was suggested by the positive correlations between maternal and neonatal leukocytes and platelets/lymphocytes ratio.